Retrospective evaluation of 155 adult equids and 21 foals with tetanus in Western, Northern, and Central Europe (2000–2014). Part 1: Description of history and clinical evolution. Issue 6 (28th September 2017) - van Galen, Gaby; Saegerman, Claude; Rijckaert, Joke; Amory, Helene; Armengou, Lara; Bezdekova, Barbora; Durie, Inge; Findshøj Delany, Rikke; Fouché, Nathalie; Haley, Laura; Hewetson, Michael; van den Hoven, Rene; et al.
Abstract: Objective: To describe clinical data of hospitalized adult equids and foals with tetanus. Design: Multicenter retrospective study (2000–2014). Setting: Twenty Western, Northern, and Central European university teaching hospitals and private referral centers. Animals: One hundred fifty‐five adult equids (>6 months) and 21 foals (<6 months) with tetanus. Interventions: None. Measurements and Main Results: Information on geographic, annual and seasonal data, demographic‐ and management‐related data, clinical history, clinical examination and blood analysis on admission, complications, treatments, and outcomes were described and statistically compared between adults and foals. The described cases were often young horses. In 4 adult horses, tetanus developed despite appropriate vaccination and in 2 foals despite preventive tetanus antitoxin administration at birth. Castration, hoof abscesses, and wounds were the most common entry sites for adults; umbilical cord infections and wounds for foals. Stiffness was the commonest observed initial clinical sign. Blood analyses frequently revealed an inflammatory response, hemoconcentration, muscle damage, azotemia, negative energy balance, liver damage, and electrolyte and acid base disturbances. Common complications or clinical signs developing during hospitalization included dysphagia, dyspnea, recumbency, hyperthermia, seizures, hyperlipemia, gastrointestinal impactions, dysuria, and laryngeal spasms. Cases were supported with wound debridement, antimicrobial treatment, tetanus antitoxin, muscle spasm and seizure control, analgesia, anti‐inflammatory drugs, fluid therapy, and nutritional support. Mortality rates were 68.4% in adult horses and 66.7% in foals. Foals differed from adult horses with respect to months of occurrence, signalment, management‐related data, potential causative events, clinical signs on admission, blood analysis, complications, and severity grades. Conclusions: This is the first study that rigorously describes a large population of equids affected by tetanus. The information provided is potentially useful to clinicians for early recognition and case management of tetanus in adult horses and foals. Tetanus affects multiple organ systems, requiring broad supportive and intensive care. Neonatal and adult tetanus in the horse should be considered as distinct syndromes, as in human medicine.